Seed micromorphology and anatomy of 36 Muscari (Asparagaceae) taxa from Turkey with notes on their systematic importance - Eroğlu, Hüseyin (Array, 2021)
This study presents the first in-depth evaluation of the morphological and anatomical characters, as well as their taxonomic importance, of the seeds of 36 taxa in subgenera Muscari, Leopoldia, Pseudomuscari and Botryanthus of the genus Muscari in Turkey, where 24 of the taxa are endemic. The results indicate that the taxa generally differ from each other in terms of seed shape and dimension. Seed dimensions vary between 1.66 mm and 3.21 mm in length, and between 1.12 mm and 2.63 mm in width. The seed surface ornamentation is grouped into nine forms: ruminate, reticulate, reticulate-areolate, reticulate-foveate, alveolate, scalariform, rugose, verrucate and areolate. The most common type is ruminate, while areolate, reticulate-foveate and scalariform ornamentation forms were found to be taxon-specific. Testa structures of the taxa examined consist in general of two different layers: the epidermis and the subepidermis in scleranchymatous or parenchymatous structures. The subepidermis may be absent in some of taxa. The structure and thickness of the epidermis and the subepidermis are very important characteristics that disclose interspecific relations among the examined taxa. We also provide a key for the identification of the studied taxa based on seed features.